Flavonoids from the Roots of Amomum compactum Soland Ex Maton (Zingiberaceae) - Deden Indra Dinata; Rani Maharani; Fauzan Zein Muttaqien; Unang Supratman; Mohamad Nurul Azmi; Yoshihito Shiono (Syarif Hidayatullah State Islamic University, 2021)
Amomum compactum Soland Ex Maton is one of the Zingiberaceae family plants which is the endemic plants from West Java, Indonesia. This study was aimed to determine the chemical structure of flavonoid compounds from n-hexane extract of A.compactum Sol. Ex Maton roots. Dried powder of the roots was extracted consecutively with n-hexane, ethyl acetate, and methanol solvents. Three flavonoids, 5-hydroxy-3,7,4`-trimethoxy kaempferol (1), 5-hydroxy-3,7,3',4'-tetra methoxy kaempferol (2) and 4'-hydroxy-3,5,7-trimethoxy kaempferol (3), have been isolated from the roots of A. compactum Sol. Ex Maton. The chemical structures of compounds 1-3 were identified by spectroscopy data including infrared 1D-NMR, 2D-NMR and HRTOF-MS as well as by comparison with previously reported spectral data. Compounds 1-3 were isolated from this plant for the first time and showed free radical DPPH scavenging activity.